Literasi Matematis Mahasiswa Calon Guru dalam Menyelesaikan Soal Numerasi Statistik Berdasarkan Gaya Belajar Honey-Mumford - Fitriyah Nabila; Hendro Permadi; Sukoriyanto Sukoriyanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2023)
This study aims to describe students' mathematical literacy skills in solving statistical literacy questions based on Honey-Mumford learning styles. The statistical literacy questions used in this study are questions of the AKM type which are related to statistical material about the size of data concentration. The subjects of this study were first semester students of the Department of Mathematics, State University of Malang. The instruments used in data collection were test questions, interview guidelines, and instrument validation sheets. The results of the study show that there are differences in the level of students' abilities in several aspects that become competencies in mathematical literacy. Students with a reflective learning style tend to be more detailed in terms of using symbols and mathematical formulas, students with a theoretical learning style tend to be more thorough in understanding and translating the meaning of the questions, while students with a pragmatic learning style tend to prefer using simple reasoning with minimal use of mathematical symbols/formulas.